SOSIALISASI PENYULUHAN TENTANG BANTUAN HIDUP DASAR (BHD) DI WILAYAH KERJA UPTD PUSKESMAS JATILUHUR KABUPATEN PURWAKARTA - Dina Hartini; Wirdan Fauzi Rahman; Reyan Budi (Bajang Institute, 2024)
Cardiac arrest and respiratory arrest are emergency situations that can lead to death if not immediately provided. Basic Life Support (BLS) is the initial action that can be taken by the community to maintain life before medical personnel arrive. However, the level of community knowledge and skills regarding BLS procedures is still low, so socialization and training are needed to improve the community's ability to deal with emergency situations. This community service activity aims to improve the knowledge and skills of the community in the work area of ​​the UPTD Jatiluhur Health Center, Purwakarta Regency in performing Basic Life Support (BLS). The method of implementation of the activity used a lecture, demonstration, and simulation approach. The activity involved 40 participants consisting of the general public and health cadres. Evaluation was carried out using pre-tests and post-tests to assess knowledge gains, as well as observation of skills during the simulation practice. The results of the activity showed an increase in participants' knowledge from an average score of 58% (pre-test) to 89% (post-test). In addition, 90% of participants were able to simulate chest compressions and artificial ventilation with the correct technique. Participants also showed high enthusiasm in participating in the entire series of activities. Basic Life Support (BLS) outreach and training have proven effective in improving the knowledge and skills of the community within the Jatiluhur Community Health Center (Puskesmas) work area. This activity is expected to be implemented sustainably to foster an emergency response community and reduce the risk of death due to delayed assistance